Albania : Detailed Assessment Report on Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2011)
In this study, antimoney laundering and counterterrorist financing measures (AML/CFT) were summarized. The measures taken to strengthen the financing system are analyzed. Albania's level of compliance with financial action task force (FATF) is assessed. Legal systems and related institutional measures are also explained. The preventive measures for financial institutions and nonfinancial businesses have also been ascribed. Finally, national and international cooperation has been discussed. The relevant issues related to AML/CFT measures have been analyzed in this paper.